The promotion of holistic care through integrative practices: a literature review (Research, Society and Development, 2023)
Introduction: through the advances and transformations of knowledge, progressively, the discourses on health and disease were based only on science, and came to represent legitimate and official knowledge, without considering the knowledge arising from popular culture. However, with the advances in research on the benefits arising from integrative and complementary health practices, it is worth highlighting the initiative of the Ministry of Health, which, with the aim of encouraging the search for new alternatives to face health problems, published the Ordinance of the Policy of Integrative and Complementary Practices in the SUS. Objective: To highlight the importance of using Integrative and Complementary Practices in promoting holistic care. Methodology: This is an integrative literature review (ILR) study, developed with the aim of gathering and synthesizing results of scientific studies. The research was carried out during the months of April and September 2022, in the Virtual Health Library and in the databases: PUBMED and CAPES. The descriptors used in the controlled research carried out were: Integrative Practices, Comprehensive Care and Health; at different times by different researchers. The following inclusion criteria were defined: full text available; document type: article; time frame from 2016 to 2022. Results and Discussion: The growing interest in PIC's can be understood as an expression of a movement that identifies with new ways of learning and practicing health, as these practices are characterized by comprehensiveness, self-care and languages unique and unique. These practices are opposed to the biomedical model, which is still rooted, and does not broaden the vision for health promotion activities, which are important both for users and for the professionals who carry them out. In Western countries, for example, medicine is conceived as a science that has the human body as its object, in which there are diseases caused by agents that must be identified so that the individual can return to his healthy state. Conclusion: Based on the above, it can be said that the inclusion of PICs in the SUS has helped to promote more humanized health spaces, which is why it is important to address them, as they seek to stimulate the natural mechanisms for preventing injuries and promoting of health through effective and safe technologies, with an emphasis on welcoming listening, the development of a therapeutic bond and the integration of human beings with the environment and society.